Nurse’s knowledge and attitude regarding cervical cancer screening at a tertiary care hospital - Pegu, Bhabani; Dhiman, Niharika; Chaturvedi, Jaya; Sharma, Suresh K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Cervical cancer is one of the commonest cancers among women which cause morbidity and mortality worldwide. Though, it is a preventable disease, most of the women with cervical cancer present in advanced stage due to lack of knowledge about the disease and screening among general population. The objective was to assess the level of knowledge and explore attitude towards cervical cancer screening among female nursing staff. Methods: A cross sectional, questionnaire based study was conducted on 34 female nursing staff in a tertiary care hospital of Uttarakhand, India in the month of January 2015. With the help of predesigned questionnaire, information was collected regarding demographic profile, knowledge about cervical cancer and attitude towards screening techniques. Results: In this study, 79% of the respondents had knowledge about screening methods for cervical cancer and 91% had knowledge about HPV vaccine. Though 82% of them were aware of pap smear and 89% had good attitude towards it, 85.29% respondent knew about colposcopy as one of the screening technique for cervical cancer. None of the respondent had undergone a pap smear themselves. Conclusions: The study showed that, female nursing staff had average knowledge and positive attitude towards cervical cancer screening. They were not aware of the routine screening guidelines and had limited understanding of different types of cervical cancer screening techniques. Hence, it is recommended that routine training should be given on regular basis to all the health care providers.